Unemployment, depression, and health: a look at the African-American community. Issue 6 (1st June 1999) - Rodriguez, E; Allen, J A; Frongillo, E A; Chandra, P
Abstract : OBJECTIVES: While the unemployment rate of African-American people is more than twice that of the white population, the research on the impact of unemployment on the health of this population is scarce. This study analysed the impact of unemployment on depression and well being among African-American people, and the factors associated with well being. METHODS: Logistic and multiple regression models were used to analyse panel data collected in the National Survey of Families and Households 1987-1992. African-American (1369) and white (6660) respondents were analysed separately. Outcome variables included an index of depression and self reported health status. MAIN FINDINGS: Differences between employment and unemployment groups were less significant for African-Americans than for the white population in predicting depression and well being. Health enhancing factors such as education and wealth were significantly associated with better health and lower depression indices among the white population but not consistently so among African-Americans. Satisfaction with personal relationships was the strongest predictor of well being for both groups. CONCLUSION: Research should focus on the special needs and circumstances of African-Americans, because protective factors may not have the same impact in different groups of the population.